The Effect of Using Audio Visual Learning Al-Qur'an Through Smart Hafidz Media on Cognition in Early Childhood - Dinda Azzahra (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
Early childhood usually spends their time playing. There are many choices of games that can be fun and make them happy. The role of parents is very important in choosing safe games for children, of course games that are useful and educational for them. One example of an educational game for children is Smart Hafiz which has the advantage of being suited to children's needs. Apart from being safe from radiation, Smart Hafiz has a lot of content that can provide lessons for children, especially Islamic religious learning which is packaged with songs, stories, and stories, which are equipped with audio-visuals so that children will enjoy and be more interactive with the learning content. Smart Hafiz is designed for children's safety and comfort so that children can play while learning in a fun, entertaining way without losing the educational element of this tool. A child's ability to read the Koran fluently is every parent's hope. In the midst of the widespread use of digital media and the rise of illiteracy, the family environment acts as the first foundation stone which becomes the main focus of education for children to eradicate illiteracy in the Koran as well as being a filter from the bad influence of technology. This research is qualitative research using content analysis and literature study methods. This research focuses on: how urgent it is to teach the Koran to children in the family environment; what are the features of learning the Koran in Smart Hafiz media; and how to use Smart Hafiz media to support the ability to read the Koran. The research results found three important aspects that parents must pay attention to when using Smart Hafiz media to be able to support children's ability to read the Al-Qur'an, including: 1) optimizing function, which emphasizes use according to correct procedures; 2) potential development, which anticipates hampering children's productivity; and 3) instilling values, which requires a direct educational touch from parents.